Edaphic and Phytochemical Factors as Predictors of Equine Grass Sickness Cases in the UK - Edwards, Sarah E.; Martz, Kathrin E.; Rogge, Anja; Heinrich, Michael (Frontiers in Pharmacology, 2010)
Background: Equine dysautonomia or equine grass sickness (EGS), as it is more commonly known, is a usually fatal disease of equids of uncertain aetiology, although associated with grazing, that affects the autonomic and enteric nervous system. Lowered gastro-intestinal motility, leading to paralysis of the gut, is one of the main symptoms of EGS. Previous studies have implicated anaerobic bacteria, notably Clostridium botulinum, but what triggers the severe bacterial infestations remains enigmatic. We hypothesized that a detailed comparison of soil mineral and botanical composition of EGS and control sites would yield new insights into the causation of the disease. Results: Between March 2007 and September 2008, soil, plant, and water samples from a total of 23 EGS sites and 11 control sites were studied. Metal and non-metal element levels of the soil and herbage samples were assessed. Significantly, EGS sites had higher levels of soil nitrogen, and significantly higher levels of iron, lead, arsenic and chromium in the herbage. Toxic Ranunculus spp. (buttercups) were found in abundance at every EGS site, making ingestion plausible. Conversely, neurotoxin-producing cyanobacteria were not found in any of the water samples analysed. Conclusions: The significantly higher levels of iron and heavy metals found in herbage growing in EGS sites, in addition to toxic Ranunculus species, suggest that previously unknown triggers are involved in a multi-factorial EGS aetiology. Our results also show that cyanobacteria on the other hand, are unlikely to be a factor in EGS. Consequently, the concomitant presence of two (or more) factors could be the trigger for an outbreak of EGS and the combination of both seems to be a key predictor.